Avaliação da qualidade da carne bovina de Nelore e Aberdeen Angus durante a maturação por Biospeckle Laser - Torres Filho, Robledo de Almeida (2015)
The objective of this study was to evaluate the use of Biospeckle laser, associated with the analysis of the biological activity, to predict the beef quality during aging by an experimental setup that enables the analysis out of an optical laboratory. The biological activity of a material, measured by the Biospeckle laser, can be expressed by a numerical parameter, the Inertia Moment (IM). The Nellore beef had (P<0.05) lower pH, sarcomere length (SL), water holding capacity (WHC) and myofibrillar fragmentation index (MFI), and higher shear force (SF) than Angus beef. Purge increased (P<0.05) up to the 14th aging day, the most pronounced case being in the Nellore beef. Cooking loss (CL) increased (P<0.05) until the 14th aging day. Only the 14th-aging-day-pH and 21 th-aging-day-SL were (P<0.05) lower than those of time zero, but remained within the range considered normal. The MFI of time zero was (P<0.05) lower than that of the 7th aging day, which was (P<0.05) lower than the MFI after 21 aging days. The MFI after 14 aging days was (P>0.05) similar to those of its adjacent times. For the evaluated aging times, the SF of following time was (P<0.05) always lower than that of the previous time due to the increased level of proteolysis (r = -0.62). The MFI was (P<0.05) positively correlated (r = 0.53), while the SF was (P<0.05) negatively correlated (r = -0.62), with aging time. The main increase in the relative content of oxymyoglobin (O2Mb) occurred (P<0.05) in the first seven aging days, with a reduction (P<0.05) in the relative content of deoxymyoglobin (Mb+). The luminosity (L*) value increased (P<0.05) slightly (1.18) until the 14th aging day only in Nellore beef. The red component (a*) value increased (P<0.05) up to the 14th aging day, but the a* value of 21 th aging day was (P>0.05) similar to those of the 7th and 14th aging days. The yellow component (b*) and saturation index (C*) values at time zero were (P<0.05) lower than those of other aging times. The IM of Nelore beef were (P<0.05) higher than those of Angus beef in the unpacked samples with temporal history speckle pattern (THSP) constructed with the center row. The aging time affected (P<0.05) IM, but without a response pattern, and with (P<0.05) weak correlations (r<0.46). The IM were correlated (P<0.05) positively with purge, CL, MFI, L*, a*, b*, C*, h* (hue angle) and O2Mb, and negatively with pH, SF, Mb+ and relative content of metmyoglobin (MMb). However, these correlations were (P<0.05) weak (-0.42<r<0.50). Therefore, the adopted setup of Biospeckle laser, associated with the IM analysis, did not achieve the expected technical potential in predicting beef quality during aging. Further studies are needed to develop the Biospeckle laser for the evaluation of beef quality in industrial conditions.